2014
DOI: 10.1002/ase.1508
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of physical therapy anatomy performance and anxiety scores in timed and untimed practical tests

Abstract: Students in health care professional programs face many stressful tests that determine successful completion of their program. Test anxiety during these high stakes examinations can affect working memory and lead to poor outcomes. Methods of decreasing test anxiety include lengthening the time available to complete examinations or evaluating students using untimed examinations. There is currently no consensus in the literature regarding whether untimed examinations provide a benefit to test performance in clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
(46 reference statements)
3
18
0
Order By: Relevance
“…Future work will, therefore, endeavor to remedy the limitations mentioned previously. As this study was exploratory in nature further projects will seek to explore the positive and negative impact this resource has on test anxiety using a more robust validated instrument, such as the State-Trait Anxiety Inventory which has been used in previous studies (Spielberger, 1983;Schwartz et al, 2015). Furthermore, due to the positive outcomes documented in this paper, and the potential for future iterations of the Facebook Page to be integrated into the anatomy curricula, a more in depth understanding of social media addiction will be conducted.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work will, therefore, endeavor to remedy the limitations mentioned previously. As this study was exploratory in nature further projects will seek to explore the positive and negative impact this resource has on test anxiety using a more robust validated instrument, such as the State-Trait Anxiety Inventory which has been used in previous studies (Spielberger, 1983;Schwartz et al, 2015). Furthermore, due to the positive outcomes documented in this paper, and the potential for future iterations of the Facebook Page to be integrated into the anatomy curricula, a more in depth understanding of social media addiction will be conducted.…”
Section: Future Directionsmentioning
confidence: 99%
“…Moreover, at present there is very little empirical research that has addressed this issue specifically within anatomy education. Schwartz et al (2015) provides a comprehensive summary on the potential impact test anxiety could have in preparation, and during, timed high-stakes assessments such as objective structured practical examinations (OSPEs). Test anxiety manifests as periods of increased worry in relation to the upcoming assessment with the student becoming distracted, and lingering negative thoughts unrelated to the actual test material (i.e., potential test failure and comparison to peers) leading to students "blanking out."…”
Section: Introductionmentioning
confidence: 99%
“…Three survey respondents reported that being timed while completing the CRI calculations while monitoring anaesthetised patients were sources of stress. Healthcare professionals also exhibit better performance on untimed tests when compared with timed tests due to reduced test anxiety 27. In critical situations during anaesthesia, delayed treatment may result in further pain and suffering to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals also exhibit better performance on untimed tests when compared with timed tests due to reduced test anxiety. 27 In critical situations during anaesthesia, delayed treatment may result in further pain and sufering to the patient. Timely and appropriate interventions without error during periods of stress are an important part of providing quality veterinary care.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of test anxiety is predominant in a broad range of disciplines and in various educational settings (Gibson, 2014). These educational settings include medicine, chiropractic, engineering, and physiotherapy fields (Powell, 2004;Saravanan, Kingston, & Gin, 2014;Schwartz, Evans, & Agur, 2015;Vitasari, Wahab, Othman, Herawan, & Sinnadurai, 2010;Zang & Henderson, 2014). In medicine, test anxiety is one of the major problems that most likely causes underachievement, low performance, demotivation, and psychological distress among their students (Powell, 2004).…”
Section: Review Of the Literaturementioning
confidence: 99%